Effectiveness of Nebulization Therapy with Chest Physiotherapy After Nebulization on Airway Clearance in Children with Bronchopneumonia - M, Denni Fransiska Helena; Nurhayati, Siti; Khotimah, Nur Intan Hayati Husnul (iora, 2023)
Bronchopneumonia accounts for 15% of all deaths of children under five. The primary nursing problem of bronchopneumonia patients is ineffective airway clearance which can lead to more severe problems such as shortness of breath and even death. Management of airway ineffectiveness can be done by nebulization and corticosteroids, chest physiotherapy, suctioning and effective coughing. Nebulization accompanied by chest physiotherapy can remove secretions or phlegm effectively. This study aims to analyze the differences in airway clearance before and after nebulization and chest physiotherapy in the control and intervention groups in bronchopneumonia children. The research design used is Quasi-Experimental. A sample of 36 respondents with bronchopneumonia children was divided into two groups, namely control and intervention groups, which were obtained by consecutive sampling. Data collection techniques used observation sheets. The data analysis used in this study is the Mann-Whitney Test. The results showed that before chest physiotherapy after nebulization, all respondents had ineffective airway clearance (100%) in both the intervention and control groups. After chest physiotherapy after nebulization, almost half of the respondents in the intervention group had adequate airway clearance (44.4%). In contrast, in the control group, a small proportion of respondents had adequate airway clearance (16.7%). The analysis showed a p-value of 0.001, meaning there is a significant difference in airway clearance after being given nebulization and chest physiotherapy interventions in the intervention and control groups. Researchers hope that in future studies, airway clearance levels can be included. Thus, chest physiotherapy is effectively used for airway clearance in children after nebulization.